Correlation between Level of Wifes Knowledge about Vasectomy and The Husband Participation in Vasectomy Program in Jaten District - Dea Fiesta Jatikusuma; Suparman .; Endang Sahir (Nexus Kedokteran Komunitas, 2015)
Background: Vasectomy program as known as MOP (Metode Operatif Pria) is a long-term contraception method that addressed for husband. From the total active participants of birth control program in Indonesia,vasectomy acceptors is only 0.7%. This low number of vasectomy acceptors can be influenced by level of wifes knowledge that form into wifes role and support toward the husband participation. The aim of this research is to examine the correlation between level of wifes knowledge about vasectomy and the husband participation in vasectomy program in Jaten District. Methods: It was an analytic observasional research with cross-sectional design in Jaten District, Karanganyar Regency to examine the correlation between level of wifes knowledge about vasectomy and the husband participation in vasectomy program. The data were taken from 387 wifes, by questionnaire that has been tested for its validity and reliability. The data analysis in this research was tested with Lambda Correlation Test in 19th version of SPSS for windows. Results: There were 271 respondents (70.03%) who had good level of knowledge, 87 respondents (22,48%) who had average level of knowledge, and 29 respondents (7.49%) who had bad level of knowledge. From the total respondents, there were only 17 respondents (4,39%) who chose vasectomy as their birth control method. The value of Lambda Correlation Test was 0.000 that showed very weak correlation between level of wifes knowledge about vasectomy and the husband participation in vasectomy program. Conclusion: There is very weak correlation between level of wifes knowledge about vasectomy and the husband participation in vasectomy program that is also known as MOP.Keywords: level of knowledge, participation in vasectomy program.